2015
DOI: 10.7554/elife.06034
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory activities of short linear motifs underlie Hox interactome specificity in vivo

Abstract: Hox proteins are well-established developmental regulators that coordinate cell fate and morphogenesis throughout embryogenesis. In contrast, our knowledge of their specific molecular modes of action is limited to the interaction with few cofactors. Here, we show that Hox proteins are able to interact with a wide range of transcription factors in the live Drosophila embryo. In this context, specificity relies on a versatile usage of conserved short linear motifs (SLiMs), which, surprisingly, often restrains th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 76 publications
(107 reference statements)
3
72
0
Order By: Relevance
“…As in our case the adjacency of Hox/Pbx binding site may identify other transcription factors that work with the Hox proteins. Because Hox proteins can interacts with many transcription factors (e.g., abd-A binds to 35; Baeza et al, 2015), they may facilitate the activation of target genes by a wide range of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…As in our case the adjacency of Hox/Pbx binding site may identify other transcription factors that work with the Hox proteins. Because Hox proteins can interacts with many transcription factors (e.g., abd-A binds to 35; Baeza et al, 2015), they may facilitate the activation of target genes by a wide range of transcription factors.…”
Section: Discussionmentioning
confidence: 99%
“…Overall our work revealed an astonishing level of functional diversity for a short conserved peptide motif, ranging from transcriptional regulation with generic or tissuespecific cofactors (11) to context-dependent nuclear export. Thus, the HX motif and its immediate surrounding region constitute a privileged platform for diversifying Hox protein function during development and evolution.…”
Section: Introductionmentioning
confidence: 92%
“…In contrast to the RhoA element that mediates Abd-A specific transcriptional activation with Pax2, the DCRE contains two binding sites for the FoxG (Slp) with both Abd-A and Ubx in embryos, and at least Abd-A does so in a manner dependent on its ability to bind DNA [47]. Moreover, the thoracic Hox factor, Antp, failed to interact with Slp2 in BiFC assays, and we previously found that instead of mediating repression Antp stimulates the DMX leg enhancer in a DCRE-dependent manner via unknown mechanisms [35].…”
Section: Hox Specificity: Target Activation Vs Target Repressionmentioning
confidence: 99%
“…Altogether, these findings are consistent with Slp2 selectively working with Ubx and Abd-A on the DCRE to mediate abdominal repression. However, it should also be noted that of the five different Hox factors tested in BiFC assays, only Antp failed to interact significantly with Slp2 [47]. Thus, it is possible that the Slp/FoxG factors are directly integrated with several Hox factors and that the specificity of output will depend upon the presence of appropriately spaced/oriented DNA binding sites within the cis-regulatory modules.…”
Section: Hox Specificity: Target Activation Vs Target Repressionmentioning
confidence: 99%